2006
DOI: 10.1007/s10620-006-9085-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune Link in the Mucosa of Chronic Gastritis with Helicobacter pylori Infection

Abstract: It is suggested that different neuropeptides regulate gastric mucosal integrity and participate in the development of chronic gastritis. The aim of this study was to examine the roles and changes of immunoreactive (IR) nerves and immunocompetent cells in human gastritis. Immunohistochemical, immunocytochemical, and confocal laser microscopic methods were used. All investigated nerve fibers were found in different quantities in the mucosa of both control and gastritis samples. The number of SP, NPY, and VIP IR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
(36 reference statements)
1
25
1
2
Order By: Relevance
“…These mediators can increase mucosal blood flow by vasodilatation [23], can activate mast cells and immunocells in the mucosa [24], and are involved in drug effects [25,26], and somatostatin can elicit systemic anti-inflammatory and analgetic "sensory functions." The immunodistribution of neuropeptides (SP, VIP, NPY, SOM, GAL, and TH) released from the sensory neurons and their neuroimmune function are known in H. pylori-positive gastritis but have not been examined in gastritis without this infection [27]. We suggest that the participation of capsaicin-sensitive afferent nerves depends on a causative factor to produce gastritis in patients, and of course Helicobacter pylori infection was especially considered as a causative factor to produce gastritis in patients.…”
Section: Introductionmentioning
confidence: 90%
“…These mediators can increase mucosal blood flow by vasodilatation [23], can activate mast cells and immunocells in the mucosa [24], and are involved in drug effects [25,26], and somatostatin can elicit systemic anti-inflammatory and analgetic "sensory functions." The immunodistribution of neuropeptides (SP, VIP, NPY, SOM, GAL, and TH) released from the sensory neurons and their neuroimmune function are known in H. pylori-positive gastritis but have not been examined in gastritis without this infection [27]. We suggest that the participation of capsaicin-sensitive afferent nerves depends on a causative factor to produce gastritis in patients, and of course Helicobacter pylori infection was especially considered as a causative factor to produce gastritis in patients.…”
Section: Introductionmentioning
confidence: 90%
“…The peripheral action of capsaicin is a dose-dependent action (Szolcsányi 1984;Mózsik et al 2001) (Table 9.5). Capsaicin releases CGRP and SP (Inui et al 1991;Dömötör et al 2005), which modifies the vascular reactions in the gastrointestinal mucosa (Sipos et al 2006) recently demonstrated that the existence of neuroimmune link between the CGRP, SP, and immune cells in the gastric mucosa of patients with chronic gastritis. Dömötör et al (2006b) demonstrated the increased release of glucagon during a sugar loading test in healthy human subjects, indicated a new step of capsaicin-induced changes taking place between the capsaicin-sensitive afferent nerves and neurohormonal regulation.…”
Section: Capsaicin-sensitive Afferentation In Patients Withmentioning
confidence: 99%
“…A klinikai vizsgálatok már igazolták, hogy SP-antagonistákkal csökkenteni lehet a gyulladást a gyomor-bél csatornában [27,28]. Számos immunsejt expresszál NPY-t indukció hatására [29,30]. Morfológiai vizsgálatok bizonyították, hogy gyulladás során az NPY-idegrostok száma szignifi kánsan megemelkedett, és nagyon közeli kapcsolatban találha-tók a szintén NPY-pozitív immunsejtekkel.…”
Section: áBraunclassified